2014
DOI: 10.1063/1.4895507
|View full text |Cite
|
Sign up to set email alerts
|

Higher harmonics generation in relativistic electron beam with virtual cathode

Abstract: The study of the microwave generation regimes with intense higher harmonics taking place in a high-power vircator consisting of a relativistic electron beam with a virtual cathode has been made. The characteristics of these regimes, in particular, the typical spectra and their variations with the change of the system parameters (beam current, the induction of external magnetic field) as well as physical processes occurring in the system have been analyzed by means of 3D electromagnetic simulation. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Taking into account these results we can assume that the inclusion of the noise in our model should lead to more developed chaos in charge dynamics in the SL under study and, thus, to the increase of bandwidth of microwave output. We believe that our findings can also be relevant to other devices, demonstrating space charge dynamics, e.g., Gunn diodes [70,71], and vacuum microwave devices with a virtual cathode [72,73]. However, this requires further investigations.…”
Section: Discussionmentioning
confidence: 97%
“…Taking into account these results we can assume that the inclusion of the noise in our model should lead to more developed chaos in charge dynamics in the SL under study and, thus, to the increase of bandwidth of microwave output. We believe that our findings can also be relevant to other devices, demonstrating space charge dynamics, e.g., Gunn diodes [70,71], and vacuum microwave devices with a virtual cathode [72,73]. However, this requires further investigations.…”
Section: Discussionmentioning
confidence: 97%
“…The simultaneous coexistence of two instabilities in a REB resulting in formation of squeezed state and beam-plasma instability leads to the complex beam dynamics in the system that may be efficiently analyzed mainly with the help of the numerical methods based on the solving of the self-consistent system of Maxwell equations and motion equations of charged particles. For that reason, the three-dimensional fully electromagnetic selfconsistent CST Particle Studio package, which has worked well in the simulation of different beam instabilities and high-power electron devices, [35][36][37][38][39][40][41][42] is used in our work for the accurate numerical investigations of physical processes in the relativistic two-section vircator model.…”
Section: System Under Studymentioning
confidence: 99%
“…[8][9][10][11] Due to mentioned space-charge phenomena, this class of HPM devices is called virtual cathode oscillators (VCOs) or vircators. 7,[12][13][14][15][16] Vircators are known to be a rather simple way to extract electromagnetic energy from relativistic electron beams (REBs) and to generate microwaves, providing high-power radiation up to a gigawatt output peak power level, or to amplify powerful microwave signals. [16][17][18][19][20][21][22] Along with advantages of VCOs such as high output power, construction simplicity, and capability to operate without application of the external magnetic field, one of the weakest points of vircators is low generation efficiency (0.1%-10%).…”
mentioning
confidence: 99%
“…7,13,26,27 Various modifications of standard vircator design have been proposed and investigated to improve microwave generation efficiency. 15,19,[28][29][30][31][32] In our opinion, one of the most interesting approaches to enhance vircator characteristics has been proposed in the early 1990s in the experimental work by Gadetskii et al 33 In this work, they have suggested the idea of the hybrid vircator and backward-wave oscillator (vircator-BWO) device. They have succeeded in the generation efficiency increase owing to creating additional electromagnetic feedback with VC by means of backward wave excitation in this device.…”
mentioning
confidence: 99%